Memory retention and recall process - Amin, H.U. (CRC Press, 2014)
Our knowledge is a collection of our experiences, which expands daily as we experience new things. The way we imbue our surroundings and ourselves with meaning depends on the knowledge and understanding we have, and this knowledge depends on our memorization of what we have learned. In daily life, we take in new information and store it in our brain, maintaining it and recalling it depending on our needs. This happens because our brain has the capability of learning new skills and experiences, storing what has been learned and reusing the stored knowledge. These capabilities of storing and reusing experiences and skills are informally known as the human memory system. Everything we do or think depends on our memory, which is active every moment, receiving new information from our senses, updating existing knowledge using focus and attention, retrieving the stored experiences and skills, and planning for future activities that have not occurred yet. Thus far, neuroscientists have been expecting to find specific stores of memory in the brain and discover their exact location to know which type of memory lies where. Unfortunately, because of the great complexity of the human brain system (Figure 10.1 1), this concept has not been proved. However, some cognitive and mental functions are found in certain brain areas. Â© 2015 by Taylor & Francis Group, LLC.